2017
DOI: 10.3126/jngmc.v13i2.16533
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between MERI and Hearing After Tympanoplasty

Abstract: Background: Chronic otitis media is otological challenge in the developing countries it is particularly single most common cause of hearing impairement. Objective: The objective of this study was to observe the impact of prognostic factor middle ear risk index on hearing of patients undergoing tympanoplasty for chronic otitis media. Methods: This was a prospective analytical study conducted in 50 patients planned for tympanoplasty for chronic otitis media and evaluation done by MERI (Middle Ear Risk Index) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
(1 reference statement)
1
5
0
Order By: Relevance
“…The present study findings were similar to a study by Naderpour et al and Sharma et al in which mean age of study subjects was 33.6 ± 7.3 years and 22.6 ± 9.1 years respectively. 9,10 Patients with COM usually have mild MERI risk scores as seen in present study. This study findings concurred with a study by Kumar et al in which 72% had mild MERI; 24% -moderate MERI and 4% had severe MERI risk scores.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The present study findings were similar to a study by Naderpour et al and Sharma et al in which mean age of study subjects was 33.6 ± 7.3 years and 22.6 ± 9.1 years respectively. 9,10 Patients with COM usually have mild MERI risk scores as seen in present study. This study findings concurred with a study by Kumar et al in which 72% had mild MERI; 24% -moderate MERI and 4% had severe MERI risk scores.…”
Section: Discussionsupporting
confidence: 69%
“…11 These findings were different as compared to a study by Sharma et al in which 64% had mild MERI score, 20% had severe MERI scores and 16% had moderate MERI scores. 10 In this study, pure tone audiogram showed that 50.77% of subjects suffered with Mild hearing impairment; 46.15% with moderate hearing impairment and 3.08% with severe hearing impairment. The present study findings were similar to a study by Muftah et al in which 37.3% of study subjects with COM had mild hearing impairment, 25.5% had moderate hearing impairment and 3.9% had severe hearing impairment.…”
Section: Discussionmentioning
confidence: 51%
“…The final score ranges from 0 to 15 and is used to categorize disease severity as normal (0), mild (1-3), moderate (4-7), and severe (8)(9)(10)(11)(12)(13)(14)(15). Pre-operative classifications of moderate and severe disease have been correlated to increased risk of tympanoplasty failure in adults, [65][66][67] but not in pediatric patients. 68 Large prospective studies, however, are still required to assess its utility in clinical practice.…”
Section: Need For Patient Stratificationmentioning
confidence: 99%
“…Patients with lower MERI had considerably better pre-operative and post-operative air and bone conduction than patients with higher MERI [ 12 ]. Hearing improved by 4 to 6 dB in persons with mild MERI.…”
Section: Reviewmentioning
confidence: 99%